1991
DOI: 10.2115/fiber.47.9_481
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Sorption of Azo Dyes Containing Fluorine Atoms by a Nylon 6 Film. Part 1. Effects of fluorine atoms on the sorption of azo dyes by a nylon 6 film.

Abstract: The sorption behavior of sodium 1-phenyl-2-hydroxy-6-naphthalenesulfonate and its deriva tives by a nylon 6 film was investigated in order to elucidate the effects of fluorine atoms. For the deriva tives, the amount of dye sorbed increased with time, and equilibrium sorption was not established even af ter the film was soaked in the aqueous dye solution for 7 days. The sorption isotherms obtained were in terpreted by considering the dual sorption mechanism which is composed of partition and Langmuir type sorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This suggests that the substituents other than the sulfonate group also influence the time dependence of the dye sorption. As was pointed out in our previous papers [3,4], Langmuir type sorption is independent of sorption time, while partition is strongly dependent. Therefore, the difference of the time dependence in the substituents is probably due to the discrepancy of the effects on the partition type sorption.…”
Section: Time Dependence Of Dye Sorptionsupporting
confidence: 55%
See 4 more Smart Citations
“…This suggests that the substituents other than the sulfonate group also influence the time dependence of the dye sorption. As was pointed out in our previous papers [3,4], Langmuir type sorption is independent of sorption time, while partition is strongly dependent. Therefore, the difference of the time dependence in the substituents is probably due to the discrepancy of the effects on the partition type sorption.…”
Section: Time Dependence Of Dye Sorptionsupporting
confidence: 55%
“…The amino end group content was determined as 3.53 X 10-5 equivalent per g of nylon by the titration of a m-cresol/methanol solution of the nylon 6 with an aqueous methanol solution of hydrochloric acid. This accurate titration showed that the amino end group content (4.65 X 10-5 eq g-1) described in the previous papers [3,4] was not correct. The nylon 6 film was pretreated in boiling water for 90 min, immersed in distilled water for 1 day, soaked in aqueous hydrochloric acid of pH3 for 1 day, and dried in a desiccator with silica gel.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations